The Role of Optometry-Nursing Teams in Closing the Gap in Geriatric Care: A Scoping Review - Alshawakir, Abdulhadi Abdullah Ali; Bander Saqer Alanazi; Amnah Hassan Ahmed Asuni; Enter Bakr Takroni; Abdullah Amer B Aldosari; Nawdh Mutair Almajdi; Kamlah Saad Alshehri; Amal Abdullah Makrami; Mutaib Abdulrahman Mukhlid Alotaibi; Al Anoud Abdullah Al Qarni; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The world’s population is rapidly aging, and an unprecedented prevalence of chronic and comorbid conditions threatens functional independence and quality of life. Optometry and nursing are often considered discrete practice disciplines, but their potential contribution to collaborative and integrated care for addressing many of these gaps remains underexplored. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The goal of this scoping review was to map the existing literature regarding interventions and care models that incorporate the combined expertise of both optometry and nursing in the management of key geriatric syndromes. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods: <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">A systematic search of electronic databases, namely, PubMed, CINAHL, Scopus, and Web of Science, was made for literature between 2014 and 2025. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results: <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">The review found a nascent but promising body of evidence. The results of the study point to three specific areas of collaboration: 1) Falls Prevention, where the nurse conducts a risk assessment and medication review in consultation with optometrist on refractive corrections; 2) Age-related Macular Degeneration (AMD) and vision impairment support where optometrist does the diagnosis and treatment, while nurses would provide psychosocial support and coaching; and 3) early signs of cognitive decline where optometrist can assess visual biomakers related to systemic health by nurses. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Optometry-nursing teams represent a powerful, patient-centered model for closing critical gaps in geriatric care. The current review aimed to summarize core components of successful collaborations and to present a conceptual framework for integration. Future research should focus on high-quality, quantitative trials to confirm efficacy and on developing standardized protocols for implementation.